Great Firewall baseline (China) - Voidly (2017)
CRITICAL severity censorship detected in China. Confidence: 95%. Data sourced from OONI, CensoredPlanet.
Censorship Incident ID: CN-2017-0001
Keywords: censorship; CN; censorship; critical